Elastic scattering and transfer reactions for the system 7Be + 58Ni at Coulomb barrier energies. (August 2015) - Mazzocco, M; Torresi, D; Acosta, L; Boiano, A; Boiano, C; Glodariu, T; Guglielmetti, A; Keeley, N; La Commara, M; Lay, J A; Martel, I; Mazzocchi, C; et al.
Abstract: We investigated the reaction induced by the Radioactive Ion Beam 7 Be on the closed proton shell nucleus 58 Ni at 22.0 MeV bombarding energy. The 7 Be beam was produced by means of the in-flight technique with the facility EXOTIC at INFN-LNL (Italy). Charged reaction products were mass and charge identified in a rather wide angular range and their energy distributions were analyzed to infer some information on the production mechanism. The relevance of direct processes, especially 3 He- and 4 He-stripping, as well as compound nucleus reactions is critically reviewed.